The Murdochian Moral Vision and the Art of Contemporary Cinema - Szőke, Dávid (Hungarian Journal of English and American Studies, 2020)
Book review: Bolton, Lucy. Contemporary Cinema and the Philosophy of Iris Murdoch. Edinburgh: Edinburgh UP, 2019. 228 pages. ISBN 9781474416399. Pbk. £75.00.